Primary Extranodal T-Cell Non-Hodgkin’s Lymphoma of the Gingiva in a HIV Patient - Joshi, Priya Shirish; Sanadi, Appasaheb; Dudanakar, Mahesh Pundalik; Bhosale, Satish Subrao (Journal of Orofacial Research, 2013)
Since the appearance of AIDS, there has been a significant increase in the number of cases of oral Non-Hodgkin’s Lymphoma (NHL). These lesions may occur in the oral cavity, but rarely appear on the gingiva. Oral HIV-related lymphomas exhibit an aggressive course and can mimic other oral tumors and infections, this can make early recognition difficult but the diagnosis is important. It is now considered that oral NHL’s serves as the first indicator of HIV infection.